IMMOBILIZATION TEST AS EVALUATING THE EFFECTIVENESS OF RESTLESS LEG SYNDROME TREATMENT ON THE BASIS OF DIABETIC POLYNEUROPATHY - Ткачук, Н. П.; Гриб, В. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
It was studied the efficiency of pramipexole treatment in patients with diabetic polyneuropathy (DPN), complicated with Restless Legs Syndrome (RLS) using immobilization test (IT). The study involved 76 patients with DPN. With major diagnostic criteria in 19 (25%) patients RLS was identified. All patients received the standard treatment of DPN and pramipexole in dose of 0.125 mg to 0.75 mg per day for 30 days. Interviews on the international RLS scale before- and 30 days after treatment. Also, IT for all patients were made. The positive effect of pramipexole in patients with RLS and DPN was found, that proven with rating scales and IT performance.